2019
DOI: 10.1021/acs.jafc.9b01239
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidation in Vitro on Structures and Functions of Myofibrillar Protein from Beef Muscles

Abstract: The main purpose of this study was to investigate the effects of oxidation in vitro on the biochemical properties of myofibrillar protein isolates (MPIs) from beef muscles. MPIs were incubated at 4 °C for 24 h with hydroxyl-radical-generating systems consisting of 0.01 mM FeCl3 and 0.1 mM ascorbic acid plus 0, 0.2, 1, 5, 10, and 20 mM hydrogen peroxide. The results showed that oxidation caused drastically structural changes in bovine MPIs. The carbonyl content, the surface hydrophobicity, and the particle diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 60 publications
10
48
0
Order By: Relevance
“…Furthermore, during the post-mortem period, endogenous proteases activity in the muscle are responsible to decrease the muscle quality (Qin et al, 2020). The role of calpain as an endogenous protease enzyme on myofibrillar proteins degradation in fish and beef muscles has been previously confirmed (Wang et al, 2011;Fu et al, 2019). Therefore, investigations on calpain activity during the post-mortem period can provide additional details about the role of this enzyme on protein degradation and also its activity in different muscle parts.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, during the post-mortem period, endogenous proteases activity in the muscle are responsible to decrease the muscle quality (Qin et al, 2020). The role of calpain as an endogenous protease enzyme on myofibrillar proteins degradation in fish and beef muscles has been previously confirmed (Wang et al, 2011;Fu et al, 2019). Therefore, investigations on calpain activity during the post-mortem period can provide additional details about the role of this enzyme on protein degradation and also its activity in different muscle parts.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies demonstrated that disulfide bonds are the primary covalent cross‐linking bonds responsible for aggregate formation (Xiong, Blanchard, Ooizumi, & Ma, 2010). A recent study identified oxidation sensitive sites in beef MPs by proteomics, suggesting that myosin, actin, calpains, and caspases are easily oxidized to form disulfide bonds due to their higher free sulfhydryl group content (Fu et al., 2019). The dityrosine bonds formation is correlated with protein sources.…”
Section: Oxidationmentioning
confidence: 99%
“…The structure of pork MPs is more easily altered at high ferric ion concentrations, and the pattern of changes is independent from the content of FeCl 3 (Park, Xiong, & Alderton, 2007). Different sources of MPs have been subjected to the Fenton system with various concentrations of H 2 O 2 and evaluated for covalent modification and their effects on gelation properties, including pork (Xia et al., 2019; Xiong et al., 2010), chicken (Liu & Xiong, 2015; Xia et al., 2018), beef (Fu et al., 2019), and fish (Li, Kong, Xia, Liu, & Diao, 2013; Lu, Zhang, Li, & Luo, 2017).…”
Section: Oxidationmentioning
confidence: 99%
“…In this sense, numerous studies have been conducted and demonstrated that a process with mild protein oxidation, at a very low oxidant concentration, for example, <1 mM H 2 O 2 , could enhance the gel properties of MP by changing the mode of myosin aggregation, which was ascribed to the shift of myosin cross‐linking in the early stage of heating from head–head association to prevalently tail–tail aggregation through disulfide bonds. While a process with excessive oxidation tended to cause larger protein aggregates, which were morphologically incapable of generating a fine gel network and instead generated a porous coagulum (Chanarat, Benjakul, & Xiong, 2015; Fu et al., 2019; Li, Li, Wang, Zhang, & Xie, 2014; Wang, He, Gan, & Li, 2018; Wang, Xiong, & Sato, 2017; Zhang et al., 2020). To elucidate the structure‐modifying effect of oxidation on the susceptibility of pork MP to MTG at 0.6 mol/L NaCl (equivalent to about 2% to 3% salt in processed meats), Li, Xiong, and Chen (2012) found that a mild oxidation process promoted the MTG‐mediated cross‐linking of MP, while a strong oxidation process inhibited the MTG effect.…”
Section: Modification Of Mpmentioning
confidence: 99%